Adaptive backstepping control of practical uncertain systems - Zhou, Jing (2008)
This thesis has addressed numerous issues pertaining to design of uncertain practical systems by using backstepping technique. Our main concern is how to develop more intelligent approaches to compensate nonsmooth nonlinear industrial characteristics, including backlash, dead-zone, hysteresis and saturation. These nonsmooth nonlinearities are common in mechanical connection, hydraulic servo valves, piezoelectric translators, electric servomotors and other industrial control systems. They often limit system performance. In this thesis it will be shown how these four nonsmooth nonlinear characteristics can be adaptively compensated and how desired system performance is achieved in the presence of such nonlinearities.